Wheater's Functional Histology A Text and Colour Atlas - Young, Barbara (Pathologist); O'Dowd, Geraldine; Woodford, Phillip (Churchill Livingston/Elsevier, 2014)
Take a simple approach to understanding the fundamentals with Wheater's Functional Histology. Offering concise text accompanied by hundreds of captions and images of histology slides, this best-selling textbook will equip you with all the must-know histology information you need to complete your courses and ace your exams.